1996
DOI: 10.1093/bja/77.6.798
|View full text |Cite
|
Sign up to set email alerts
|

Randomization is important in studies with pain outcomes: systematic review of transcutaneous electrical nerve stimulation in acute postoperative pain

Abstract: We set out to examine the evidence for the importance of randomization of transcutaneous electrical nerve stimulation (TENS) in acute postoperative pain. Controlled studies were sought; randomization and analgesic and adverse effect outcomes were summarized. Forty-six reports were identified by searching strategies. Seventeen reports with 786 patients could be regarded unequivocally as randomized controlled trials (RCT) in acute postoperative pain. No meta-analysis was possible. In 15 of 17 RCT, we judged ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
16

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(99 citation statements)
references
References 35 publications
0
80
1
16
Order By: Relevance
“…We know that if trials are of poor reporting quality, 17,18 or not randomised, 30 or not blind, or both, 31 then the tendency is to overestimate the benefits of treatment. The reviews included here all demanded that trials should be both randomised and double-blind as a minimum requirement for inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…We know that if trials are of poor reporting quality, 17,18 or not randomised, 30 or not blind, or both, 31 then the tendency is to overestimate the benefits of treatment. The reviews included here all demanded that trials should be both randomised and double-blind as a minimum requirement for inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…TENS is of limited benefit as a stand alone treatment for severe to moderate pain but may be useful in combination with pharmacotherapy. Systematic reviews on TENS and postoperative pain and labour pain have reported negative outcomes (7,8). A meta-analysis demonstrated that TENS reduced post-operative analgesic consumption and that adequate TENS technique was critical to outcome (9).…”
Section: Tens and Acute Painmentioning
confidence: 99%
“…14 38 39 Surgical stress is a physiological reaction that produces endocrine, immune and haematological changes, which may contribute to negative outcomes and subsequent morbidity. Prominent among these changes are a rise in pancreatic secretion of glucagon and of liver glycogenolysis and gluconeogenesis, reduction of insulin release and rise in blood glucose.…”
Section: Discussionmentioning
confidence: 99%